Contemporary gothic and horror film : transnational perspectives - McDonald, Keith (Anthem Press, 2021)
This book examines contemporary Gothic cinema within a transnational approach by focusing on the aesthetic and philosophical roots which lie at the heart of the Gothic. The study will invoke its literary and filmic forebears by exploring how these styles informed the modern filmic Gothic.